A joint replenishment competitive location problem - Silva, Francisco (2019)
Competitive Location Models seek the positions which maximize the market captured by an entrant firm from previously positioned competitors. Nevertheless, strategic location decisions may have a significant impact on inventory and shipment costs in the future affecting the firm’s competitive advantages. In this work we describe a model for the joint replenishment competitive location problem which considers both market capture and replenishment costs in order to choose the firm’s locations. We also present an metaherusitic method to solve it based on the Viswanathan’s (1996) algorithm to solve the Replenishment Problem and an Iterative Local Search Procedure to solve the Location Problem.